The carbon footprint and energy consumption of liver transplantation - De Simone, Paolo; Lai, Quirino; Ducci, Juri; Campani, Daniela; Biancofiore, Giandomenico (Frontiers in Transplantation, 2025)
Background and aimsThere is growing interest in the environmental impact of surgical procedures, yet more information is needed specifically regarding liver transplantation. This study aims to quantify the total greenhouse gas emissions, or carbon footprint, associated with adult whole-size liver transplantation from donors after brain death, including the relevant back-table graft preparation.MethodsThe carbon footprint was calculated retrospectively using a bottom-up approach. This approach sums the volumes of energy consumption (kWh), volatile anesthetics (ml), solid waste (kg), and units of blood products transfused for each transplant. These consumption values were converted using validated conversion factors to the equivalent mass of carbon dioxide released into the environment (kg CO2e).ResultsA total of 147 patients with a mean age of 55 years (male, 78.9%) who underwent liver transplants between 2021 and 2022 were analyzed, resulting in 45.5 tons CO2e. The mean (SD) carbon footprint for each procedure was 309.8 (33.2) kg CO2e [95% CI: 304.4; 315.3]. Total energy power consumption was 96.5 MW, contributing 65.4% of greenhouse emissions (29.8 tons CO2e), while volatile anesthetics, solid waste, and blood product transfusions contributed 8.0% (3.64 tons CO2e), 5.9% (2.7 tons CO2e), and 20.6% (9.4 tons CO2e), respectively. The duration of surgery (t = 29.0; p < 0.001), transfused red blood cells (t = 13.1; p < 0.001), fresh frozen plasma (t = 11.1; p < 0.001), platelets (t = 8.9; p < 0.001), and the use of an extracorporeal pump machine (t = 3.6; p < 0.001) had the greatest effects on greenhouse gas emissions.ConclusionsLiver transplantation requires significant energy and is associated with considerable greenhouse gas emissions, particularly during longer procedures. Transplant clinicians, hospital administrators, policymakers, and patients should be aware of the environmental impact of liver transplantation and collaborate to adopt sustainable energy practices.